Explorations Into the Viability of High Voltage Bipolar Na-Ion Cells Using Liquid Electrolytes - Rudola, Ashish; Wright, Christopher J.; Barker, Jerry (Frontiers in Energy Research, 2022)
Bipolar electrodes can be defined as electrodes where cathode and anode active materials exist on either side of a shared current collector substrate. The resultant rechargeable bipolar batteries, using series-connected electrochemical cells within one sealed enclosure, can enable high-voltage systems irrespective of the voltage of the cathode//anode couple used. The sodium-ion battery, being well-suited for the bipolar concept, is now rapidly being commercialized and has higher energy densities than most rechargeable battery technologies. However, bipolar sodium-ion batteries using commercially-feasible liquid electrolytes and manufacturing methodologies, have not been demonstrated at scale yet. Herein, we explore the design methodology needed to enable commercial realization of such bipolar sodium-ion batteries, using liquid electrolytes and different types of cathode//anode couples. We show good cycling stabilities over 200 cycles and potential for voltages beyond 6 V for bipolar Na-ion pouch cells. We also introduce a scalable method to fabricate nSmP Na-ion/mixed-chemistry bipolar cells (n cells in series; m cells in parallel) in a single, sealed cell. Our results point to realistic promise for high voltage and sustainable bipolar sodium-ion batteries.